ANALISIS PERENCANAAN PENCEGAHAN PENYAKIT DIARE BERBASIS LINGKUNGAN DI WILAYAH KERJA PUSKESMAS POASIA - Wa Ode Salmiati; Ramadhan Tosepu; Suhadi Suhadi (Universitas Halu Oleo, 2019)
This study aims to analize and find out (1) characteristics of the incidence of diarhea disease and basic sanitations to diarrhea disease and basic on the environment in the region Poasia Health Center, (2) Of the condition of the distribution of basic sanitation based on spatial analysis as diarrhea. (3) The relationship between of the distribution of basic sanitation and the incidense of diarrheal diseases in the Poasia Health Center. (4) Environmental based diarrhea prevention planning in the Poasia Health Center area. The objectives of this study were all housholds living in the Poasia Health Center working area of 6.464 HHs and the sample in this study was 323 households. Determination of respondents in this study using random sampling . Data collection using ovservations, interviews adn quetioners. Data analysis uses Univariate, Bivariate and Spatial analysis.The result shows of (1) The characteristics of basic sanitation convering the condition of the means clean water condition councillor family. The condition of the trash dumpsite of the and conditions sewer water was unqualified is factors cause did not the spread of the diarrhea disesse (2) Environmental condition of the Health Center Poasia be seen from the fulfillment to sanitation classified as good enought (3) The means clean water and councillor family dont related with imcident diarrhea while means drainpipe water waste and the means trash dunpsite of the associated with the incident diarrhea. (4) The planning of disease prevention diarrhea work area Health Center Poasia is not just pay attention to the aspects of sanitation basic, but seen from the cultural aspekcs of economy and aspecks of goverment policy integrated and carried out coordinated that created environment clean and healthfully. Keywords: Diarrhea, Planning, Prevention, Basic Sanitation